Management Of Entrepreneurship Education In Realization Entrepreneurial Students (Multisite Study At The LPI Al Azhaar Islamic Boarding School, Tulungagung And The Modern Islamic Boarding School Sumberdaya At Taqwa (Pomosda) Nganjuk) - Prasetyo Winarto, Dedy; Yatnaningtias, Niken; Ari Laksono, Tio (International Journal of Educational Research & Social Sciences, 2024)
Islamic boarding schools have an important opportunity to solve society's economic problems, especially in overcoming the problem of unemployment which has been a polemic. One way that Islamic boarding schools can develop entrepreneurial intelligence is by integrating entrepreneurship education into the boarding school system. This research uses a phenomenological approach with a multisite study design. Phenomenological research aims to describe, describe, and report a situation, object, or event without drawing general conclusions. This research found that in integrating entrepreneurship education into Islamic boarding school education, it is necessary to plan it every year to determine the road map for the entrepreneurship education program. They are combining the government or formal school curriculum with entrepreneurship education. Carry out activity programs in accordance with the vision, mission, and work program. Carry out synergy and collaboration with stakeholders related to entrepreneurship education, both government institutions and private institutions. Supervision is carried out by checking the results of entrepreneurship education in Islamic boarding schools. Corrective action is taken if the process and work results have not been achieved as specified, but if the process and work results are appropriate then what must be done is an improvement.